Tuberculoid lymphadenitis due to Mycobacterium chelonei - Morris, C. A. (1973)
An 8-year-old boy developed cervical lymphadenitis four months after an injection of dental anaesthetic. Histology of the lymphatic tissue showed a tuberculoid granulomatous reaction with scanty acid-fast bacilli. Mycobacterium chelonei was isolated in pure culture (NCTC 10882). The patient showed specific skin hypersensitivity to an extract of M. chelonei, but not to that of M. ranae. This is thought to be the first recorded case of lymphadenitis in man caused by M. chelonei; it adds another possibility to be considered in the differential diagnosis of `a lump in the neck'.